Climate change and water resources - Shrestha, Sangam; Babel, Mukand S.; Pandey, Vishnu Prasad (CRC Press, Taylor & Francis Group, 2014)
"Written by expert authors from around the world, this book examines the full scope of climate change science, the impacts on the water sector, and all available mitigation and adaptation strategies. Each chapter provides an analysis of the issues raised and is supported by appropriate examples and case studies. With a broad scope of related topics, this book is useful to a wide range of readers who are directly or indirectly working with climate change and water issues"-- Provided by publisher